2017
DOI: 10.1155/2017/8401074
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds, Antioxidant Capacity, and Fatty Acids in Different Parts of Four Unexplored Fruits

Abstract: Total phenolic content (TPC), total flavonoids (TF), total anthocyanins (TA), and antioxidant capacity of different parts of four unexplored fruits from Brazil (Syzygium cumini Lam, Solanum nigrum Linn, Inga edulis Mart, and Hovenia dulcis Thunb) were determined; the bioactive compounds and fatty acids were quantified and identified by high-performance liquid chromatography and gas chromatography, respectively. S. cumini peels contained the most TA (63.31 mg/100 g), whilst H. dulcis pulp and peels had the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
0
9
0
2
Order By: Relevance
“…Indeed, the antioxidant abilities of PPPs were stronger than that of polysaccharides obtained from Hovenia dulcis [8], and were positively related to their contents of polyphenolics (Table 1 and Figure 3), which further confirmed that the bonded polyphenolics could be one of the main contributors to the antioxidant abilities of PPPs [19,40]. Indeed, some phenolic compounds in PPPs determined by UPLC-Q-TOF-MS possess obvious in vitro antioxidant activities, such as gallocatechin [41], kaempferol [42], myricetin [43], and quercetin [44]. Previous study has also revealed that the main mechanisms for the antioxidant activities of polyphenols might be the metals chelation, the H-atom transfer, and the electron transfer [45].…”
Section: In Vitro Antioxidant Activitiesmentioning
confidence: 55%
“…Indeed, the antioxidant abilities of PPPs were stronger than that of polysaccharides obtained from Hovenia dulcis [8], and were positively related to their contents of polyphenolics (Table 1 and Figure 3), which further confirmed that the bonded polyphenolics could be one of the main contributors to the antioxidant abilities of PPPs [19,40]. Indeed, some phenolic compounds in PPPs determined by UPLC-Q-TOF-MS possess obvious in vitro antioxidant activities, such as gallocatechin [41], kaempferol [42], myricetin [43], and quercetin [44]. Previous study has also revealed that the main mechanisms for the antioxidant activities of polyphenols might be the metals chelation, the H-atom transfer, and the electron transfer [45].…”
Section: In Vitro Antioxidant Activitiesmentioning
confidence: 55%
“…15,16 According to Bampi et al 13 the peduncles are rich in sugars and have a high content of dietary fiber. In addition, the peduncles are known to be a rich source of antioxidant compounds [17][18][19][20] as well as exhibit pharmacological activities, e.g. improve the alcoholic hepatic steatosis and inflammation via regulation of lipid and inflammation metabolism 21 and have preventive effects…”
mentioning
confidence: 99%
“…22 However, as far as we know, food applications and the fatty acid composition of the seeds were poorly studied, with a single work recently published. 20 According to Rydlewski et al 20 the seeds are a rich source of PUFAs, and 53% of the total lipids (TL) correspond to LNA. Based on that, the seeds of the Japanese grape are also a potential new source of n-3 PUFAs.…”
mentioning
confidence: 99%
“…Free radical species in general is Reactive Oxygen Species (ROS) and Reactive Nitrogen Species (RNS) (Wojcik et al 2010). Presence of free radicals is causes of degenerative diseases such as arthritis, atherosclerosis, cancer, diabetes, and parkinson's (Rydlewski et al 2017). Preventing and minimizing the impact of free radicals is needed antioxidants (Huang et al 2013).…”
Section: Introductionmentioning
confidence: 99%